The Status of Ābirū in Contemporary Iranian Shīʿī Narratives = mfhūm « ālāʾābrū » ūmkānth fī ālrūāīāt ālšīʿīa ālāʾīrānīa ālmʿāṣra - Rodziewicz, Magdalena (Journal of Islamic ethics, 2022)
The current study elaborates on the place, status and functions of the concept of ābirū in Shīʿī religious discourse in contemporary Iran. Its main source material has been selected from a variety of rulings (fatwās) and other type of statements delivered by Iranian marājiʿ taqlīd (sources of emulation). By emphasizing the significance of the concept of ābirū in the Iranian tradition and its reception within the Shīʿī tradition, this study outlines the main functions attributed to the idea of ‘good reputation’ and ‘positive social image’ in contemporary Iranian religious jurisprudence. The analysis of the rulings issued by Iranian clergy allows one to distinguish how the idea of ābirū influences verdicts in different aspects of the life of a believer - personal, ethical, legal and political. The study reveals the flexible way in which this moral concept is being incorporated into judgements which, in turn, may result in a novel and nuanced understanding of many Islamic principles, especially in socio-political perspectives.